Frühneuhochdeutsches Wörterbuch - Arbeitsstelle der Akademie der Wissenschaften zu Göttingen,,Goebel, Ulrich,Lobenstein-Reichmann, Anja,Reichmann, Oskar (De Gruyter, 2016)
Das Frühneuhochdeutsche Wörterbuch ist ein alphabetisch geordnetes Bedeutungswörterbuch der Varietäten des Hochdeutschen des 14. bis 17. Jahrhunderts The Early New High German Dictionary is an alphabetically-ordered dictionary of the varieties of High German from the 14th to 17th century
10.1515/9783110491463
Keywords: German language / Early modern; 1500-1700 / Dictionaries; Early New High German; Frühneuhochdeutsch; Wörterbuch; dictionary; LANGUAGE ARTS & DISCIPLINES / Reference